Post sterilization of intraoral scan body and the effect it has on the axes and distances between three adjacent implants: in-vitro study - Gil Ben-Izhack; Diva Lugassy; Ofir Rosner; Joseph Nissan; Shir Rachmiel; Yara Khoury; Asaf Shely (BMC, 2024)
Abstract Background The purpose of this pilot in-vitro study was to assess the effect of sterilization on the intra-implant axis, inter-implant axis, intra-implant distance and inter-implant distance of three implants in a straight line by using laboratory scanner (LBS) versus intra-oral scanner (IOS) with intra-oral scan bodies (ISB). Methods: A printed 3D model with three internal hex analogs in the positions 15#,16#,17# was used. Zirkonzhan (ZZ) intra-oral scan body (ISB), two-piece titanium was used. The ZZ ISBs were scanned by 7 Series dental wings (LBS) and 30 times by Primescan (IOS) pre sterilization and 30 times post sterilization. For each scan (pre and post) stereolithography (STL) file was created and a comparison between all the scans pre sterilization and post sterilization were superimposed on the laboratory scan by using a 3D analyzing software. A Kolmogorov-Smirnov test performed followed by Wilcoxon Signed Ranks tests. (p < 0.05) Results: Post sterilization of the ZZ ISB, the mean errors were significantly increased for the inter-implant distances (p < 0.0005), intra-implant distances 1,2,3 (p < 0.0005), intra-implant axis 1,3 (p < 0.0005) and inter-implant axes 13,23 (p < 0.05). In contrast, the mean errors for intra-implant axis 2 (p < 0.0005) and inter-implant axis 12 (p < 0.0005) were significantly reduced. Conclusions: ZZ ISB showed changes in all four parameters after sterilization. The middle ISB had the largest changes in mean error regarding all four parameters. Sterilization process may affect the three-dimensional (3D) structure of the ZZ ISB after three cycles. There is a lack in the literature in this field and there is a need for further studies to explore the effect of sterilization (multiple cycles) on different ISBs and for creating an approved guidelines regarding the amount of sterilization for each ISB in the industry.